Afiksasi dalam Bahasa Mori - Siti Fatinah (Balai Bahasa Sulawesi Tengah, 2020)
Affixation in Mori language has various forms and functions. The research studies about how the form and function of affixation in Mori language are. The research intends to describe the form and function of affixation in Mori language. The method used in collecting data is the participatory method. The data is analyzed using the intralingual correspondence method through the substitution technique. The result of research illuminates that the form of affixation in Mori language is classified as prefixation, infixation, suffixation, con-fixation, and affixation combined. There are eight prefixations found, such as moN-, meN-, poN-, te-, pe-, in-, poko-, and um-. MoN- and poN- prefixation are embedded either in the base form or prefixed word. Infixations found are -in- and -um. Infixation -in- is embedded either in the base form or in the affixed form. Suffixation found consists of three suffixation, namely -o, -a, and -i. in Mori language, confixation are three, they are a-a, po-a, and pe-a. Combinations of affixation are five, affixation of moN-ako, meN-ako, i-in, in-ako, and in-i. Affixation aforementioned functions to form verb and affixed noun. Besides, affixation also functions to change part of the speech of the base form and confirms the meaning of its base form.